Complete reperfusion mitigates influence of treatment time on outcomes after acute stroke. (12th April 2016) - Prabhakaran, Shyam; Castonguay, Alicia C; Gupta, Rishi; Sun, Chung-Huan J; Martin, Coleman O; Holloway, William; Mueller-Kronast, Nils H; English, Joey; Linfante, Italo; Dabus, Guilherme; Malisch, Tim; Marden, Franklin; et al.
Abstract : Background: Time to reperfusion following endovascular treatment (ET) predicts outcomes after acute ischemic stroke (AIS). Objective: To assess the time–outcome relationship within reperfusion grades in the North American Solitaire Acute Stroke registry. Methods: We identified patients given ET for anterior circulation ischemic stroke within 8 h from onset and in whom reperfusion was achieved. Together with clinical and outcome data, site-adjudicated modified Thrombolysis in Cerebral Ischemia (TICI) was recorded. We assessed the impact of time to reperfusion (onset to procedure completion time) on good outcome (modified Rankin Scale 0–2 at 3 months) in patients who achieved TICI 2 or higher reperfusion in multivariable models. We further assessed this relationship within strata of reperfusion grades. A p<0.05 was considered significant. Results: Independent predictors of good outcome at 3 months among those achieving TICI ≥2a reperfusion (n=188) were initial National Institutes of Health Stroke Scale score (adjusted OR=0.90, 95% CI 0.85 to 0.95), symptomatic hemorrhage (adj. OR=0.16, 95% CI 0.05 to 0.60), TICI grade (TICI 3: adj. OR=11.52, 95% CI 3.34 to 39.77; TICI 2b: adj. OR=5.14, 95% CI 1.61 to 16.39), and time to reperfusion per 30 min interval (adj. OR=0.91, 95% CI 0.82 to 0.99). There was an interaction between final TICI grade and 30 min time to reperfusion intervals (p=0.001) such that the effect of time was strongest in TICI 2a patients. Conclusions: Time to reperfusion was a strong predictor of outcome following ET for AIS. However, the effect varied by TICI grade such that its greatest effect was in those achieving TICI 2a reperfusion.